Identification of barriers to decarbonise the German steel industry as a basis for a feasibility assessment - Robin König; Thomas Pregger; Stefan Kronshage; Patrick Jochem (Energy Policy, 2026)

Decarbonization of urea production in India and its impact on water withdrawal and costs: A cost optimization approach - Nikhil Dilip Pawar; Kunal Singhal; Chandra Bhushan; Thomas Pregger; Patrick Jochem (Journal of Cleaner Production, 2025)

Industrial and infrastructural conditions for production and export of green hydrogen and synthetic fuels in the MENA region: insights from Jordan, Morocco, and Oman - Sibel Raquel Ersoy; Julia Terrapon-Pfaff; Thomas Pregger; Josua Braun; El Mostafa Jamea; Ahmed Al-Salaymeh; Patrick Braunschweig; Zsuzsa Bereschi; Oana Teodora Ciobotaru; Peter Viebahn (Sustainability Science, 2024)
Green hydrogen and synthetic fuels are increasingly recognized as a key strategic element for the progress of the global energy transition. The Middle East and North Africa (MENA) region, with its large wind and solar potential, is well positioned to generate renewable energy at low cost for the production of green hydrogen and synthetic fuels, and is therefore considered as a potential future producer and exporter. Yet, while solar and wind energy potentials are essential, other factors are expected to play an equally important role for the development of green hydrogen and synthetic fuels (export) sectors. This includes, in particular, adequate industrial capacities and infrastructures. These preconditions vary from country to country, and while they have been often mentioned in the discussion on green hydrogen exports, they have only been examined to a limited extent. This paper employs a case study approach to assess the existing infrastructural and industrial conditions in Jordan, Morocco, and Oman for the development of a green hydrogen and downstream synthetic fuel (export) sector.

Future renewable energy targets in the EU: Impacts on the German transport - Danial Esmaeili Aliabadi; Katrina Chan; Niklas Wulff; Kathleen Meisel; Matthias Jordan; Ines Österle; Thomas Pregger; Daniela Thrän (Transportation Research Part D: Transport and Environment, 2023)

Moving towards socio-technical scenarios of the German energy transition—lessons learned from integrated energy scenario building - Thomas Pregger; Tobias Naegler; Wolfgang Weimer-Jehle; Sigrid Prehofer; Wolfgang Hauser (Climatic Change, 2020)